A non-viral genome editing platform for site-specific insertion of large transgenes - Chaudhari, Namrata (2021)
Background: The precise, functional and safe insertion of large DNA payloads into host genomes offers versatility in downstream genetic engineering-associated applications, spanning cell and gene therapies, therapeutic protein production, high-throughput cell-based drug screening and reporter cell lines amongst others. Employing viral- and non-viral-based genome engineering tools to achieve specific insertion of large DNA-despite being successful in E. coli and animal models-still pose challenges in the human system. In this study, we demonstrate the applicability of our lambda integrase-based genome insertion tool for human cell and gene therapy applications that require insertions of large functional genes, as exemplified by the integration of a functional copy of the F8 gene and a Double Homeobox Protein 4 (DUX4)-based reporter cassette for potential hemophilia A gene therapy and facioscapulohumeral muscular dystrophy (FSHD)-based high-throughput drug screening purposes, respectively. Thus, we present a non-viral genome insertion tool for safe and functional delivery of large seamless DNA cargo into the human genome that can enable novel designer cell-based therapies. Methods: Previously, we have demonstrated the utility of our phage λ-integrase platform to generate seamless vectors and subsequently achieve functional integration of large-sized DNA payloads at defined loci in the human genome. To further explore this tool for therapeutic applications, we used pluripotent human embryonic stem cells (hESCs) to integrate large seamless vectors comprising a ‘gene of interest’. Clonal cell populations were screened for the correct integration events and further characterized by southern blotting, gene expression and protein activity assays. In the case of our hemophilia A-related study, clones were differentiated to confirm that the targeted locus is active after differentiation and actively express and secrete Factor VIII. Results: The two independent approaches demonstrated specific and functional insertions of a full-length blood clotting F8 expression cassette of ~ 10 kb and of a DUX4 reporter cassette of ~ 7 kb in hESCs. Conclusion: We present a versatile tool for site-specific human genome engineering with large transgenes for cell/gene therapies and other synthetic biology and biomedical applications.